Social and Cultural Specifics of the Pomor Linguistic Consciousness (Sailors and Fishermen of North Arkhangelsk) - Alexandrovna Sidorova, Tatyana; Evgenievna Morozova, Olga; Evgenievna Kotsova, Elena; Sergeevna Bolgova, Natalia; Nikolaevna Ivanishcheva, Olga (International Journal of Engineering and Technology, 2018)
The research subject of this article is the professional vocabulary used by the Arkhangelsk Pomors that has not been thoroughly studied yet. This article aims to fully describe the social and cultural specifics of the linguistic consciousness revealed in the social dialect of coast-dwellers (the Pomors) and their "cultural heirs", sailors and fishermen of North Arkhangelsk. The material source is the professional vocabulary and recorded oral speech of the social dialect used by coast-dwellers and documented in the three-volume dictionary of the popular-colloquial speech of Arkhangelsk. The article also considers such ambiguous terms as professional vocabulary, the Pomors and linguistic consciousness. The authors of the article have used the integrative approach to material analysis: cognitive, sociolinguistic and linguistic. The dominant analysis was chosen as the main research method. Notional dominants are understood as mental structures of consciousness that correlate with group values and regulate interpretative activities of the Arkhangelsk Pomors in the process of nominating real-life objects. The notional dominants of the Pomor social and cultural linguistic consciousness are as follows: reality specification, respect for professional experience and labor as a need, setting for the figurative perception of reality, etc. It is proved that intentional modality is a specific modal component of the Pomor linguistic consciousness. The research has established that the knowledge connected with linguistic means is socially significant since it marks peculiar features of the linguistic consciousness typical of the social dialect. Sailors and fishermen formed the linguistic world-image correlated with social and cultural perception and interpretation. The authors of the article have revealed and described such concepts as LABOR, MAN and NATURE associated with the basic concept of the Pomor social dialect – SEA. The authors have also specified cognitively prominent levels of the Pomor linguistic consciousness.